Kinerja Aparat Desa dalam Penyelenggaraan Pemerintahan di Desa Pantai Labu Pekan - Nur’aini Muslim; Irwan Nasution (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2014)
Issues raised in this study were: (1) Performance village officials in governance at the village Pantai Labu Pekan Subdistrict Pantai Labu, (2) Obstacles and barriers village official duties in improving governance in the Village Pantai Labu Pekan Subdistrict Pantai Labu, (3 ) The efforts barriers village official duties in improving governance in the village of Pantai Labu Sub Distrik Pantai Labu District of Deli Serdang. This study uses a qualitative description of data analysis methods that take the study site on Coast Village Office District of Coast Pantai Labu Pekan. Source of data in this study is the head of the village and local villagers. Data were collected by interviews and documentation. The results of this study indicate that the performance of the Village Administrative District of Coast Pantai Labu Pekan Sub-Distrik Pantai Labu in terms of the governance process that emphasizes teamwork, discipline, creativity and responsibility have not been able to provide maximum services that fit the needs of the community.